A Mencian Account of Resentment. Issue 9 (4th August 2022) - Ooi, Daryl
Abstract: The reactive attitude of 'resentment' has been gaining increasing attention within contemporary philosophical literature. However, little attention has been given to the conceptions of resentment in Asian philosophy. In recent years, some philosophers have argued that there is a positive account of resentment in Confucian philosophy. This paper brings a recent Confucian account of resentment in conversation with contemporary philosophical discussions. The conversations revolve around aspects of resentment such as exculpatory conditions, payback, transition, and moral cultivation. The conversation not only adds clarity to the Mencian account, it also demonstrates potential contributions this account has to contemporary discussions on resentment.